ANALISIS KERAGAMAN GENETIK KENTANG HITAM - Kusumadewi Sri Yulita; Fajarudin Ahmad; Diyah Martanti; Yuyu S. Poerba; Herlina Herlina (Research Center for Biology-Indonesian Institute of Sciences, 2014)
Kentang hitam [Plectranthus rotundifolius (Poiret) Sprengel] of family Lamiaceae is a minor root crop known only for people living in some parts of Java, Bali and Madura. It was rarely found in its natural habitat, thus it was assumed to have low level of genetic diversity. This present study aimed to assess genetic diversity of 63 accessions of kentang hitam from provenances of Java based on Inter Simple Sequence Repeats (ISSR) and Random Amplified Polymorphic DNA (RAPD) fingerprints. Ten primers of ISSR and RAPD were initially screened and eight were selected for the analysis. These eight primers (OPA13, OPB10, OPB13, OPD8, OPN14, UBC 807, 834 and 835) generated 61 bands with an average of 7.63 polymorphic fragment per primer. Percentage of polymorphism ranged from 8.20% (UBC 807 and 834) to 16.39% (OPB 10) with an average of 12.50%polymorphism.Clustering analysis was performed based on ISSR and RAPD profiles using the neighbour joining method and Principle Coordinate Analysis (PCO). The range of genetic similarity among accessions was 51-100% to which most of the accessions were clustered with more than 80% similarity. This confirmed our hypothesis of the low level of variation existed among accessions.